Advances in solar sailing - Macdonald, Malcolm (Springer Praxis Books, 2014)
Hosted by the Advanced Space Concepts Laboratory within the department of Mechanical and Aerospace Engineering of the University of Strathclyde, the third International Symposium on Solar Sailing was held in McCance Building at 16 Richmond Street, Glasgow, between 11 and 13 June 2013. The symposium attracted over 90 delegates from19 different counties, bringing together international experts from across the globe to discuss funded solar sail flight programs alongside on-going technology development and testing programs. The symposium also provided a forum for the discussion of enabling technologies, new application concepts, materials and structural concepts, space environmental effects, dynamics, navigation, control, and much more. This volume contains the unabridged symposium proceedings, in the gathered experts own words. As symposium chair, I thank our partners at Scottish Enterprise and L'Garde, Inc., the symposium's gold sponsor, for their support in realising this symposium.